The effect of mortar and bond type on mechanical parameters of masonry walls - Yetkin, Musa; Calayir, Yusuf; Alyamac, Kuersat Esat (Gazi Univ, Fac Engineering Architecture, 2024)
Purpose: We investigated the effect of mortar and bond type on the mechanical parameters of masonry walls. We examined the effect of steel fiber reinforced mortar and joint thickness as mortar type. Steel fiber mortars were 0%, 1%, 2% and 3% by weight. Joint thicknesses were 1 cm, 2 cm and 3 cm. We used three different bond types (stack bond, 1/2 stretcher bond and 1/3 stretcher bond). Accordingly, we created 108 masonry wall elements in total. We subjected these wall elements to the diagonal compression test (Figure A). Theory and Methods: We experimentally investigated the effect of steel fiber reinforced mortar, different joint thicknesses and bond types on the mechanical parameters of masonry walls. We created wall elements for 36 different types. We subjected these walls to the diagonal compression test. Results: As a result of the tests; it has been determined that cracks occur along the loading direction and for walls formed with fibrous mortars, the length of this crack decreases as the fiber content in the mortar increases. The wall elements created with non-fibrous mortars suddenly collapsed when they reached their maximum load values. No such collapse was observed in the walls formed with fibrous mortars. The masonry walls using non-fibrous mortars have lower values in terms of mechanical parameters than walls using fibrous mortars. The masonry walls in which the stretcher bond types are used are the walls that have higher values in terms of mechanical parameters compared to the walls in which the stack bond type is used. When the joint thickness is compared, it has been determined that the highest numerical values in terms of mechanical parameters occur on walls with a joint thickness of 2 cm. Conclusion: The wall elements created by using steel fiber mortar exhibited a better behavior than the other walls in terms of collapse pattern. This clearly shows the positive effect of steel fiber on the collapse behavior of masonry walls. The highest numerical values in terms of mechanical parameters were obtained for the mortars containing 2% micro steel fiber, 2 cm joint thickness and walls with 1/2 stretcher bond type, respectively.
Yığma duvarların mekanik parametrelerine harç ve örgü tipinin etkisi
Keywords: Masonry walls; Steel fiber reinforced mortar; Joint thickness; Bond type; Diagonal compression test